Prevalence of malnutrition using the GLIM criteria and a knowledge, attitudes and practices assessment in newly diagnosed cancer patients and healthcare professionals in a private healthcare setting, Namibia - Botha, Theo-Anne (Stellenbosch : Stellenbosch University, 2021)
Thesis (MNutr)--Stellenbosch University, 2021.